Law Enforcement of Alcohol Consumption in Children (Case Study of Puhpelem District, Wonogiri Regency) - Abdul Harist Rifai; Hanifah Febriani (Universitas Muhammadiyah Surakarta, 2023)
There have been many criminal acts or crimes that are present and occur in our society due to the consumption of alcohol, some of which kill many people at once. In this era of times and shifting globalization requires many people to be more careful in everything, especially parents who already have children. Free association and no strong fortress make children vulnerable to associations that are not at their age, such as alcohol. This becomes polemic when a child chugs alcohol and the one who gives access is an adult, who should be an adult who can be a good example for a child. This research uses Juridical-Empirical research methods with the object of research in Puhpelem District, Wonogiri Regency. In some cases in Puhpelem sub-district, several children were found drinking alcohol. This research will describe the regulation of alcohol in Indonesia and law enforcement against children who consume alcohol in Puhpelem District. The data obtained came from interviews with members of the Puhpelem police station, a community leader, and a village head.